Opinie studentów Rzeszowa o problematyce kryzysu migracyjnego - Moczuk, Eugeniusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Europe is witnessing a migration crisis as a result of a significant influx of hundreds of thousands of people coming to Europe, both fleeing the effects of the war and coming for economic reasons. The social consequences of the situation are difficult to assess. Undoubtedly, refugees have the right to move to countries deemed safe, however, the region where the refugees arrive has the right to maintain its centuries-old social, cultural, religious and economic identity. The aim of the study is to present the results of the research conducted among the students of Rzeszow universities concerning their attitudes towards the migration crisis. The research shows that the respondents are aware of the differences between refugees and migrants, but also notice the existence of threats resulting from uncontrolled migration to the country.